Hyodeoxycholic acid modulates gut microbiota and bile acid metabolism to enhance intestinal barrier function in piglets - Chong, Jie; Zhou, Yongming; Li, Zhi; Li, Xiaokai; Zhang, Jinwei; Cao, Haoran; Ma, Jideng; Ge, Liangpeng; Zhong, Hang; Sun, Jing (Frontiers in Veterinary Science, 2025)
Oral bile acids, particularly hyodeoxycholic acid (HDCA), serve as critical drivers for gut microbial community maturation in mice. In the first study, Cy5-labeled HDCA combined with fluorescence imaging revealed rapid gastrointestinal transit of HDCA in piglets, contrasting with its delayed absorption observed in mice. In the second study, the effects of the oral HDCA supplementation on microbiota-host metabolic interactions were investigated using four piglet model groups: OPM-HDCA (naturally born, raised germ-free (GF), and orally administered HDCA), OPM-CON (naturally born, raised GF, and orally administered PBS), SPF-HDCA (naturally born, raised GF, and received fecal microbiota transplantation (FMT) and HDCA), and SPF-CON (naturally born, raised GF with FMT but no HDCA). The results demonstrated that HDCA administration at 0.2 mg/mL suppressed body weight gain in piglets, which was alleviated by FMT. HDCA significantly altered gut microbiota composition in SPF piglets, markedly increasing the Lactobacillus abundance (37.97% vs. 5.28% in SPF-CON) while decreasing the proportion of Streptococcus (28.34% vs. 38.65%) and pathogenic family Erysipelotrichaceae (0.35% vs. 17.15%). Concurrently, HDCA enhanced intestinal barrier integrity by upregulating tight junction proteins (ZO-1, Claudin, Occludin) and suppressing pro-inflammatory cytokines (TNF-α, IL-1β). Additionally, HDCA significantly upregulated ileal gene expression of CYP7A1 (cytochrome P450 family 7 subfamily A member 1) and TGR5 (G protein-coupled bile acid receptor 1) in both SPF-HDCA and OPM-HDCA groups compared to their respective controls (p < 0.05). These findings demonstrate that HDCA exerts microbiota-dependent effects on growth performance, intestinal barrier function, and bile acid metabolism in piglets. Although 0.2 mg/mL HDCA treatment suppressed body weight gain, it potentially enhanced intestinal barrier integrity by activating the TGR5 signaling pathway and increasing the abundance of beneficial bacteria such as Lactobacillus. These results also highlight the critical role of early-life gut microbiota in nutritional interventions, providing a basis for developing precision nutritional strategies targeting intestinal microbial ecology in piglets.